Semi-sharp Creases on Subdivision Curves and Surfaces - Kosinka, J.; Sabin, M. A.; Dodgson, N. A. (Computer graphics forum, 2014)
We explore a method for generalising Pixar semi‐sharp creases from the univariate cubic case to arbitrary degree subdivision curves. Our approach is based on solving simple matrix equations. The resulting schemes allow for greater flexibility over existing methods, via control vectors. We demonstrate our results on several high‐degree univariate examples and explore analogous methods for subdivision surfaces.